Frontiers of textile materials : polymers, nanomaterials, enzymes, and advanced modification techniques - Shabbir, Mohd (Chemist); Ahmed, Shakeel; Sheikh, Javed N. (John Wiley & Sons, Inc., 2020)
"The book 'Frontiers and Textile Materials' deals with the important materials that can be utilized for value-addition and functionalization of textile materials. The topics covered in this book include the materials like enzymes, polymers, etc. that are utilized for conventional textile processing and the advanced materials like nanoparticles which are expected to change the horizons of textiles. The futuristic techniques for textile processing like plasma are also discussed. The text reviews advances in smart textiles, e.g. flexible electronics such as nanogenerators and solar cells into textiles matrix to design wearables. Also, it examines materials for textile, from manufacturing to finishing. Focuses on materials of natural origin and discusses alternatives of conventional finishing"--